Markell and Voge's medical parasitology - John, David T.; Petri, William A. (Saunders Elsevier, 2006)
The text explores arthropods both as parasites in their own right and as vectors or intermediate hosts for other parasites so students can understand the direct and indirect impact that they have on health. Advances in this field are reflected in the modifications of this text. New life cycle drawings are included. Halftone illustrations with color plates.